Dispersal ability determines the scaling properties of species abundance distributions : a case study using arthropods from the Azores - Borda-de-Água, Luis (2018)
Submitted by Paulo Borges (pborges@uac.pt) on 2018-03-22T12:23:53Z No. of bitstreams: 1 105_Borda-De-Agua_Scientific_Reports_2017.pdf: 4148115 bytes, checksum: 7aebefc02fa1c3321323635deef3db5c (MD5)